Pesantren for World Peace (A Case Study in a Pesantren in Jombang) - Ali Makhrus; Rizki Amalia (International Journal Ihya' 'Ulum al-Din, 2020)
The issues of terrorism and radicalism emerge in almost all countries in the world. Acts of violence based on intolerance - religious, cultural, social- bring drastic consequences and often lead to a humanitarian crisis. Hate narratives, drastic changes of social order, poverty, and injustices influence people, especially youth, to be easily attracted by radical ideology. As a result, destructing church and other worship places, even killing non-Muslims become massive agendas held systematically and planned as the name of jihad. The wrong way to understanding Islam supporting peace and tolerance brings extremist people to have a perception that non-Muslim blood is halal. As a country with Muslims as the majority society, Indonesia needs to do comprehensive and systematic agendas to prevent young generations from radical ideology. Pesantrens as a reliable Islamic institution that have played significant roles in promoting peace and tolerance since many years ago need to have innovative ways to promote world peace. This study aimed to explore the role of a Pesantren in Jombang to promote world peace through conducting an international interfaith event namely ASEAN Youth Interfaith Camp involving 94 youths from many countries. This study was qualitative research using interview, observation and document analysis as tools to gather data. This study found that the Pesantren promote world peace through an international event involving credible speakers, and bringing the participants to visit some religious places and meeting various religious adherents. This paper hopefully could be an inspiration for other pesantrens in promoting world peace.